Eufemism in Environmental Discourse of the Movement Capital Country in Indonesian Mass Media: Critical Ecolinguistics - Rachmad Fadillah Maha; Dwi Widayati; T. Thyrhaya Zein (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
In its presentation, the mass media use various language tools to package environmental discourse, one of which is euphemism. This study highlights the phenomenon of the use of euphemisms contained in the environmental discourse of moving the country's capital city in the mass media in Indonesia. This research is a qualitative descriptive study. The data was taken from online news portals, namely Kompas.com, Okezone.com, and Detik.com using the listening method with an advanced technique in the form of note taking. The data is limited only around the context of the transfer of the country's capital. Data analysis is done interactively and continues continuously until complete. The euphemism expression unit used by the mass media in Indonesia in the discourse of the transfer of the country's capital is divided into four, namely words, phrases, clauses, and sentences. Units of expression in the form of words, namely in the form of the basic words noun and adjective nits of expression in the form of derivative words are divided into three, namely noun, adjective, and drab. Euphemism units of expression take the form of phrases, namely noun phrases and adjective phrases. Units of expression in the form of clauses and sentences found only one variation. The euphemism categorization found in ten data, namely one for one subtitutions, flippancy, generale for specific, remodeling, colloquial, understatement, circomlucation, acronym, metaphor, and clipping. Euphemism.